Leucaena psyllid research grants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A limited number of research grants are available from the Forestry/Firewood Research Development Project to support work on the control of psyllids in leucaena. Applicants should limit proposed budgets to less than US $ 4000; priority will be...